Comparison of propofol monotherapy and propofol combination therapy for sedation during gastrointestinal endoscopy: A systematic review and meta‐analysis. Issue 5 (17th April 2018) - Yoon, Sang Won; Choi, Geun Joo; Lee, Oh Haeng; Yoon, Il Jae; Kang, Hyun; Baek, Chong Wha; Jung, Yong Hun; Woo, Young Cheol
Abstract : Background and Aim: Previous randomized controlled trials have reported conflicting findings comparing propofol combination therapy (PCT) with propofol monotherapy (PMT) for sedation of patients undergoing gastrointestinal endoscopy. Therefore, a systematic review was carried out to compare the efficacy and safety of PCT and PMT in such patients. Methods: We searched MEDLINE, EMBASE and CENTRAL databases to identify all randomized controlled trials that compared the efficacy and safety of PCT and PMT for sedation of patients undergoing gastrointestinal endoscopy. Primary endpoints were incidence of respiratory complications, hypotension and arrhythmia, dose of propofol used, and recovery time. Procedure duration and the satisfaction of patients and doctors were also evaluated. Results: A total of 2250 patients from 22 studies were included in the final analysis. The combined analysis did not show any difference between PCT and PMT in the incidence of respiratory complications (risk ratio [RR], 0.80; 95% CI, 0.52 to 1.23; I 2 = 58.34%), hypotension (RR, 1.06; 95% CI, 0.63 to 1.78; I 2 = 72.13%), arrhythmia (RR, 1.40; 95% CI, 0.74 to 2.64; I 2 = 43.71%), recovery time (standardized mean difference [SMD], 0.16; 95% CI, −0.49 to 0.81; I 2 = 95.9%), procedure duration (SMD, 0.04; 95% CI, −0.05 to 0.14; I 2 = 0.0%), patient satisfaction (SMD, 0.13; 95% CI, −0.26 to 0.52; I 2 = 89.63%) or doctor satisfaction (SMD, 0.01; 95% CI, −0.15 to 0.17; I 2 = 0.00%). However, the dose of propofol used was significantly lower in PCT than in PMT (SMD, −1.38; 95% CI, −1.99 to −0.77; I 2 = 97.70%). Conclusion: PCT showed comparable efficacy and safety to PMT with respect to respiratory complications, hypotension and arrhythmia, recovery time, procedure duration, patient satisfaction, and doctor satisfaction. However, the average dose of propofol used was higher in PMT.